2021
DOI: 10.3390/ijms22147357
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of “Omic” Studies to the Understanding of Cadasil. A Systematic Review

Abstract: CADASIL (Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy) is a small vessel disease caused by mutations in NOTCH3 that lead to an odd number of cysteines in the epidermal growth factor (EGF)-like repeat domain, causing protein misfolding and aggregation. The main symptoms are migraines, psychiatric disorders, recurrent strokes, and dementia. Omic technologies allow the massive study of different molecules for understanding diseases in a non-biased manner or even for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Lacunar infarcts are one of the distinctive markers of SVD, including both sporadic [16] and monogenic SVD types (such as cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) [48][49][50]) and other rare hereditary diseases [51]. In histopathological studies of lacunar infarcts, the perforating arteries typically show thickening of the media, lipohyalinosis, segmental arterial disorganization, and fibrinoid degeneration [18].…”
Section: Chronic Hypoperfusionmentioning
confidence: 99%
“…Lacunar infarcts are one of the distinctive markers of SVD, including both sporadic [16] and monogenic SVD types (such as cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) [48][49][50]) and other rare hereditary diseases [51]. In histopathological studies of lacunar infarcts, the perforating arteries typically show thickening of the media, lipohyalinosis, segmental arterial disorganization, and fibrinoid degeneration [18].…”
Section: Chronic Hypoperfusionmentioning
confidence: 99%
“…The unusual association of lacunar stroke with vertigo could be due to the usual lesional topography of lacunar strokes in the centrum semiovale, internal capsule, basis pontis, and ventroposterolateral thalamic nucleus, which are all cerebral structures that are remote from the central vestibular connecting pathways [ 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular functions or biological processes of the proteins included ECM constituents, cytoskeleton, protein processing and vesicular traffic, and cell adhesion. 144 In a comparative postmortem proteome profiling analysis of two brain arteries in patients with the p.Arg1031Cys NOTCH3 mutation, Arboleda-Velasquez et al 114 identified 19 proteins whose levels differed significantly between patients with CADASIL and controls. Most of them were ECM proteins that were significantly increased in patients with CADASIL such as collagen 1α2, collagen12α1, collagen14α1, collagen18α1, laminin α5, laminin γ1, lactadherin, clusterin, vinculin, leucine-rich repeat proteoglycan, and perlecan.…”
Section: Biomarkers For Cadasilmentioning
confidence: 99%